Prevalence of Autism Spectrum Disorder in 7–9-Year-Old Children in Denmark, Finland, France and Iceland: A Population-Based Registries Approach Within the ASDEU Project - Delobel-Ayoub, M.; Saemundsen, E.; Gissler, M.; Ego, A.; Moilanen, I.; Ebeling, H.; Rafnsson, V.; Klapouszczak, D.; Thorsteinsson, E.; Arnaldsdóttir, K.; Roge, B.; Arnaud, C.; et al. (Journal of Autism and Developmental Disorders, 2019)
International audience We estimated autism spectrum disorder (ASD) prevalence in 7-9 year-old children in 2015 using data from three nationwide health registry systems (Denmark, Finland, Iceland) and two French population-based regional registries. Prevalence ranged from 0.48% in South-East France to 3.13% in Iceland (South-West France: 0.73%, Finland: 0.77%, Denmark: 1.26%). Male/female ratios ranged from 3.3 in Finland to 5.4 in South-West France. Between 12% (Denmark) and 39% (South-West France) of cases were diagnosed with intellectual disability. The variations in population-based ASD prevalence across four European countries with universal health care practices likely reflect variation in detection, referral and diagnosis practices and autism awareness across these areas. Using established population-based data systems is an efficient approach to monitor ASD prevalence trends over time.